Expression of sfa and afa Genes in Uropathogenic Escherichia coli Under Probiotic Effect - Khalid, Amina Nabeel; Abu-Resha , Rasmiya Abd (Al-Rafidain Journal of Medical Sciences ( ISSN 2789-3219 ), 2024)
Background: Urinary tract infections (UTIs) are primarily caused by Escherichia coli. Various genes in UPEC isolates are considered virulence factors that cause illness in humans. Objective: To identify the adhesive genes sfa and afa in UPEC strains isolated from UTI patients that form biofilm and to investigate the impact of probiotics (Lactobacillus acidophilus) on their expression. Methods: Between October and December 2023, 140 samples were obtained from Urinary Tract Infection (UTI) patients and urinary catheter specimens at Al-Yarmouk Hospital and Ghazi Al-Hariri Hospital for Surgical Specialties locations in Baghdad, Iraq. All bacterial isolates were identified using the VITEK-2 system and standard biochemical testing. The isolates were subsequently subjected to PCR to detect adhesive genes sfa and afa using primers that were specifically designed. The MRS broth was centrifuged, and Lactobacillus acidophilus extract was obtained as a result. Then, isolates that contained two genes were subjected to a Lactobacillus acidophilus extract test. Results: The formation of biofilm of UPEC isolates was (33.33%) a strong biofilm-former, (61.90%) a moderate biofilm, and (4.76%) a weak biofilm. The sfa and afa genes were present at a frequency of 80.95% and 14.28%, respectively. At least one adhesive gene was present in most isolates. Conclusions: Most of the isolates showed a decrease in the expression of sfa and afa genes because of the effect of L. acidophilus on gene expression.